Technology Acceptance Model (TAM) on Banking: A Review - Mimma Maripatul Uula; Sherrindra Avedta (SMART Insight, 2023)
This study aims to see the development of Technology Acceptance Model (TAM) on Banking research around the world and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme